Design of A QR Code-Based Food and Beverage Ordering Application for Restaurants - Muh. Rahman Firmansyah; Alicia Amelia Elizabeth Sinsuw; Arie. S. M. Lumenta (Syntax Idea, 2026)
The rapid advancement of information technology has accelerated digital transformation across various sectors, including the culinary industry. However, many restaurants still rely on manual ordering systems, which often lead to order inaccuracies, service delays, and inefficient data management. This study aims to design a QR Code-based food and beverage ordering application for restaurants. The proposed system enables customers to access menus, place orders, and complete transactions directly through their smartphones without requiring a login process. Meanwhile, administrators can manage orders and monitor sales data in real-time through a web-based dashboard. The system is developed using the Rapid Application Development (RAD) method to ensure a fast and iterative design process that aligns with user needs. The results indicate that the designed system can improve service efficiency, reduce ordering errors, and enhance the overall customer experience in restaurant operations. In conclusion, the proposed QR Code-based ordering system is proven effective in addressing manual ordering problems at Coto Maros restaurant. The implications of these findings provide practical contributions for culinary business owners in adopting digital technology to improve operational efficiency, as well as serving as a reference for developing similar systems in other business sectors.